(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Acharya Kashyapa in Revatikalpa adhyaya explained about the Jataharinies, as a group of demons who has divine vision, attack women to destroy or to produce serious problems of menstrual cycle, recurrent abortions, still birth, intrauterine fetal death, neonatal deaths or severe disorders which decreases the life span of the fetus. As recurrent miscarriage, intrauterine death of an infant or death at birth has always been a devastating experience for the mother and of concern in clinical practice. All these mortality remains a challenge in the care of pregnant women worldwide, particularly for those who had history of adverse outcome in previous pregnancies (BOH). Antiphospholipid antibody syndrome (Hughes syndrome) is an autoimmune, hypercoagulable state caused by antiphospholipid antibodies. Pregnancy related complications are miscarriage, still birth, preterm delivery, IUD etc. This is one of the few treatable causes of pregnancy loss, and successful pregnancy rates of 70% or more can be achieved with appropriate treatment. Description of Jataharinies resemble with APLA, hence critical analysis will help to emphasize on management of Jataharinies by Ayurvedic treatment principles.